Enhanced Donor–π–Acceptor Character of a Porphyrin Dye Incorporating Naphthobisthiadiazole for Efficient Near‐Infrared Light Absorption. Issue 20 (24th March 2018) - Higashino, Tomohiro; Kurumisawa, Yuma; Nimura, Shimpei; Iiyama, Hitomi; Imahori, Hiroshi
Abstract : Donor–π–acceptor (D–π–A) molecules play an important role in various fields including polymer solar cells (PSCs) and dye‐sensitized solar cells (DSSCs). In PSCs, naphtho[1, 2‐ c :5, 6‐ c′ ]bis[1, 2, 5]thiadiazole (NTz) has emerged as a promising acceptor owing to its higher electron‐accepting ability compared with 2, 1, 3‐benzothiadiazole (BT), which is a widely used acceptor unit in DSSCs as well as PSCs. On the other hand, various D–π–A‐type porphyrin dyes have been developed for use in DSSCs and have achieved high power conversion efficiencies ( η ). Given that enhanced D–π–A character improves light‐harvesting ability in the near‐infrared (NIR) region, we have designed and synthesized for the first time a novel D–π–A‐type porphyrin sensitizer, ZnPNTz, incorporating the NTz unit. The porphyrinZnPNTz shows excellent absorption in the NIR region together with a large Stokes shift as a result of the NTz moiety. A DSSC fabricated withZnPNTz exhibits photocurrent generation at wavelengths up to 860 nm. Therefore, we have demonstrated that the NTz unit is a promising electron‐acceptor unit for novel D–π–A small molecules exhibiting unique optical properties in the NIR region. Abstract : We have designed and synthesized for the first time a novel D–π–A‐type porphyrin sensitizer incorporating a naphtho[1, 2‐ c :5, 6‐ c′ ]bis[1, 2, 5]thiadiazole (NTz) unit. Owing to the strong electron‐accepting ability of the NTz unit, the porphyrin shows excellent absorption in the NIR region and the DSSC fabricated from this sensitizer exhibits photocurrent generation at wavelengths up to 860 nm.